2017
DOI: 10.1371/journal.pone.0178588
|View full text |Cite
|
Sign up to set email alerts
|

Vowel production of Mandarin-speaking hearing aid users with different types of hearing loss

Abstract: In contrast with previous research focusing on cochlear implants, this study examined the speech performance of hearing aid users with conductive (n = 11), mixed (n = 10), and sensorineural hearing loss (n = 7) and compared it with the speech of hearing control. Speech intelligibility was evaluated by computing the vowel space area defined by the Mandarin Chinese corner vowels /a, u, i/. The acoustic differences between the vowels were assessed using the Euclidean distance. The results revealed that both the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…Generally, the F2s of corner vowels in cochlear implant speakers are more divergent and lower than that of normal hearing speakers, resulting in horizontally compressed vowel space (20) . Similarly, another study (29) found that the vowel space is more compressed in cochlear implant individuals compared to those of normal hearing. In both studies (20,29) , the reduction of the vowel space decreased the speech intelligibility of individuals.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Generally, the F2s of corner vowels in cochlear implant speakers are more divergent and lower than that of normal hearing speakers, resulting in horizontally compressed vowel space (20) . Similarly, another study (29) found that the vowel space is more compressed in cochlear implant individuals compared to those of normal hearing. In both studies (20,29) , the reduction of the vowel space decreased the speech intelligibility of individuals.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, another study (29) found that the vowel space is more compressed in cochlear implant individuals compared to those of normal hearing. In both studies (20,29) , the reduction of the vowel space decreased the speech intelligibility of individuals.…”
Section: Discussionmentioning
confidence: 78%
“…It is important to consider that the hearing loss present in the patient may have influenced speech production. A study evaluated the production of vowels in speakers with different hearing loss levels by comparing them with normal-hearing speakers and found a reduced articulatory working space in the group with conductive and mixed hearing losses when compared with the control group, indicating less intelligible speech 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent linguistics work (Hung, Lee, & Tsai 2017) reports that the inter-speaker variation among D/HH people in Taiwan Mandarin shows /i/ varying acoustically along the dimension of anteriority, /a/ varying along the dimension of verticality, and /u/ varying the least. It is found that /i/ is the most acoustically variable among the three corner vowels across both D/HH speakers and hearing speakers (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…It is found that /i/ is the most acoustically variable among the three corner vowels across both D/HH speakers and hearing speakers (Figure 1). This work also suggested that variability of /i/ does not seem to be a physiological product of deafness; instead, they proposed it may be due to the difference in signal conduction methods, in that people who rely on bone rather than air to conduct sounds may hear ‘distorted’ /i/ sounds that are located at lower frequencies (Hung et al 2017). Considering the style axiom, intra-speaker variation usually derives from and echoes the variation which exists between speakers (Bell 1984).…”
Section: Methodsmentioning
confidence: 99%